Direct trocar access: a safe method to create pneumo peritoneum, experience from GI and minimal access surgery unit, RIMS, Imphal - V., Sreejith; Lohe, Yepeto; Tripathi, Vidyanand; Ansari, Arshad; Marak, Angela B.; Moirangthem, G. S. (International Surgery Journal, 2019)
Background: The establishment of pneumoperitoneum is a prerequisite for all laparoscopic surgeries. The standard techniques of creating pneumoperitoneum are open and closed technique. Recent studies showed, complications associated with Veress needle insufflation such as gas embolism, sub cutaneous emphysema etc. Hasson’s method has shown to minimise vascular injuries but doesn’t reduce bowel injuries along with gas leak and port instability. The present study was conducted to assess the safety and efficacy of direct trocar insertion in patients undergoing elective laparoscopic procedures. Methods: The present study was conducted prospectively on 476 patients undergone various laparoscopic abdominal procedures using direct trocar access to create pneumo peritoneum during a period from May 2014 to July 2017 in unit 1 of Department of Surgery, RIMS, Imphal, India. Results: All patients age varying from 14 to 70 years are included. The average time taken from skin incision to create pneumoperitoneum was 1 mt. However, author is unable to use this technique in 4 patients having central obesity and switched on to conventional Veress needle for creating pneumoperitoneum. No injuries to bowel, vessels and other insufflation related complication were encountered. Conclusions: No technical difficulty was encountered while inserting trocar directly. No intra-abdominal injuries of bowel, mesentery or vessel were detected. Intra operatively all patients were found to be stable hemodynamically. Post-operatively and on follow up no port site complication such as infection, granuloma formation, induration and herniation were encountered.